STRUCTURAL REINFORCEMENT OF OLD BUILDINGS FOR ADDITIONAL FLOORS IN SERANG CITY - Era Agita Kabdiyono; Andrian Saputro; Agung Prio Laksono (Jurnal Ilmiah Teknik, 2025)
Indonesian students face significant challenges in managing their academic lives due to busy class schedules, tight assignment deadlines, and the need to collaborate effectively. This condition is exacerbated by the limitations of digital tools that are not specifically designed to address the specific needs of Indonesian students. This study aims to develop the EduKring application as an innovative solution that is able to integrate academic schedule management, real-time task reminders, and collaboration between students in one platform. The Design Thinking method was used in this study, involving five main stages: empathize, define, ideate, prototype, and test. Surveys and interviews were conducted to understand student needs, generate creative ideas that were realized in application prototypes, which were then tested using the System Usability Scale (SUS) method. The test results showed an average SUS score of 75.75, which reflects a good level of usability and is acceptable to the majority of users. These findings indicate that EduKring meets students’ needs in managing their time and academic collaboration more effectively. However, this study also identified room for improvement, especially in terms of user interface (UI) design and user experience (UX). Further development will focus on improving feature personalization, refining visual design elements, and adding interactive functions to increase user engagement. With a user-centric approach and continuous iteration, EduKring is expected to make a significant contribution to improving the quality of higher education in Indonesia through innovative technology integration.